Elevation of modulus and elongation of semicrystalline polyurethanes. Issue 18 (29th August 2018) - Zhai, Jinxian; Wamuo, Onyenkachi; Zhao, Weiwei; Tao, Xueyu; Hsu, Shaw Ling; Slark, Andrew
ABSTRACT: Polyurethanes were synthesized based on an amorphous polyester polyol, and different chain extenders, comparing the universally accepted symmetric chain extender (1, 4‐butanediol) with an asymmetric (1, 2‐propanediol) chain extender. The effect of incorporating a crystalline polyester polyol polyhexamethylene adipate (PHMA) was investigated. The resulting morphologies and tensile properties are dramatically different. Based on the thermal and infrared data obtained, the sample with the symmetric chain extender exhibits a phase‐separated morphology, which can change as a function of time and temperature. Conversely, the polyurethane with the asymmetric chain extender has a phase mixed morphology that remains stable under the same experimental conditions. Incorporating crystalline PHMA resulted in a substantial change in the mechanical properties of the materials, especially for the copolymer comprising asymmetric chain extender. The rate of crystallization and the degree of crystallization achieved depended on the type of chain extender used. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018 Abstract : This study deals with the effects of different chain extenders on the morphology development and tensile properties of polyurethanes including semicrystalline polyols. The intent is to elucidate the relationship between the structure of the chain extender on the crystallization kinetics and the degree of crystallinity achieved, thus providing an explanation of the different mechanical properties measured.